#HereToStay: murals of resistance and civic engagement. Issue 2 (4th March 2021) - Rodriguez, Darlene Xiomara; Tuschling, Lina
ABSTRACT: Visual art provides a platform for activists to make political standpoints, highlight social struggles, and reinforce collective identities in a silent, yet powerful way. Protest art is a form of non-violent action that allows expressions of dissent and inspires change. Murals are a unique form of protest because they are in public spaces and reach a large audience that is then exposed to political and social critiques, often highlighting past and present injustices. In this article, we introduce the work of Yehimi Cambrón as a case study. Cambrón is an artist living in Atlanta, Georgia where her murals depict historic and current issues by mingling Atlanta's rich history of the civil rights movement with her personal story of being an undocumented immigrant. We analyse her work through the lens of non-violent theories and in the context of street art and protest murals that have brought awareness to a variety of cultural, structural, and violent conflicts. In line with the literature on protest art and non-violent action, we argue that murals like the ones from Cambrón are a form of non-violent civic action that give voice to marginalized groups by using publicly visible space to confront social and political issues.